Ethics of ideals and "prose of life" in Panteleimon Kulish's epistolary - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article from a series of publications about the prominent Ukrainian writer, publisher, translator and author of Ukrainian spelling, the so-called "kulishivka", is dedicated to the analysis of the author's worldview constants reflected in his epistolary. The ethical maxims and moral principles of Panteleimon Kulish are considered as the unity of the ideal, inspired by creative, romantic views of the author and real life. P. Kulish's appeals are analyzed from the point of view of his motivation for dominant evaluations of events, circumstances and characteristics of the addressees, such as attitude towards work, people, culture, language, history, etc. Particular attention is paid to the influence of M. Gogol on P. Kulish due to the fact that P. Kulish was the author’s commentator, archiver of texts and memoirs as well as publisher. The letters give an opportunity to chronologize and explain P. Kulish's meetings with M. Gogol's family, an assessment of M. Gogol's creativity by his contemporaries, to find out the peculiarities of work on M. Gogol's texts and the memories of his confederates and P. Kulish’s friends. The analysis of the epistolary introduces P. Kulish’s seek for spiritual truths, comparisons and parallels with M. Gogol's reflections and creative sources, in particular during his visit to Danilov Monastery and to the writer's tomb.  P. Kulish's intellectual reflection in epistolary texts reveals a complex of ethical problems around which the author always focuses, substantiating the complexity of views on the issues of "ideal" – "profane", "people" – "service to people", "gospel truths" – "the world of real people", "the commensurability of the gospel word" – "living spiritualized nature " etc. A wide range of P. Kulish addressees is analyzed, which allows us to observe the panorama of the cultural life of the Ukrainian intelligentsia in the mid-19th century, testing in the environment of cultural and public figures of traditional ethical views and formation of new ideas about language, culture and national revival. P. Kulish's general characterization of moral principles is correlated with his appeals to authoritative figures, iconic events and partial manifestation in epistolary texts, in particular the features of requests to addressees. The author concludes that P. Kulish’s personality was complex and ambiguous. At the same time, the writer was a tireless worker who combined high ethical ideals with the moral principles of creative life – the service of the word.
Keywords: Panteleimon Kulish’s epistolary, epistolary as text, ethical maxims, P. Kulish's moral principles, Mykola Gogol’s ethical dominants, P. Kulish’s addressees, language in P. Kulish's worldview, ideal truths and real life, gospel word and nature.